TRANSFORMASI UMKM KULIT JAWA BARAT: KAPASITAS SERAP, INOVASI, DAN KINERJA ORGANISASI - Toha Rianto (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to analyze the effect of absorptive capacity and ability to innovate on organizational performance in Micro, Small, and Medium Enterprises (MSMEs) of leather crafts in West Java. This study uses a quantitative approach with a causal and explanatory design. Data were collected from 33 MSME owners of leather crafts spread across 27 cities and districts in West Java through questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS3 software. The results of the study indicate that absorptive capacity has a significant effect on organizational performance. The ability of MSMEs to recognize, assimilate, and apply external knowledge effectively has been shown to improve business performance. In addition, the ability to innovate also has a significant effect on organizational performance. Innovation allows MSMEs to create new products, improve quality, and respond to market changes adaptively and competitively. This study concludes that investment in strengthening organizational learning capacity and sustainable innovation systems is essential to improving the competitiveness of MSMEs of leather crafts in West Java.